Optimalisasi Gerakan Literasi Keagamaan di Kalangan Siswa Madrasah Ibtidaiyah - Akhmad Syahri (Faculty of Education and Teacher Training, Institut Agama Islam Negeri Pekalongan, 2020)
In more recent years, religious literacy among students is assumed to be low. There is also limited amount of research has been conducted on this area. This study aims to find out the practice of religious literacy movements among students of Madrasah Ibtidaiyah. This study belongs to qualitative research and uses case study as its research design. The data were collected through interview, observation, and documentation. The result shows that the optimization of religious literacy movement among students can be built through clear programs and regulations, adequate facilities, and measurable learning. The construction of Albert Bandura's social learning model also applied in the religious literacy movement among students of Madrasah Ibtidaiyah. It includes modeling, stimulating, learning from reality or experience, as well as being dialogical and not patronizing. The religious literacy movement of students can be categorized into optimal when the students have the character of